A Global Equilibrium Asset Pricing Model with Home Preference - Solnik, Bruno; Zuo, Luo (Management Science, 2012)
We develop a global equilibrium asset pricing model assuming that investors suffer from foreign aversion, a preference for home assets based on familiarity. Using a utility formulation inspired by regret theory, we derive closed-form solutions. When the degree of foreign aversion is high in a given country, investors place a high valuation on domestic equity, which results in a low expected return. Thus, the model generates the simple prediction that a country's degree of home bias and the expected return of its domestic assets should be inversely related. Our predicted relation between the degree of home bias and a country's expected return has the opposite sign predicted by models that assume some form of market segmentation. Using International Monetary Fund portfolio data, we find that expected returns are negatively related to home bias. This paper was accepted by Brad Barber, Teck Ho, and Terrance Odean, special issue editors.